HUBUNGAN WOMEN INDEPENDENCE DENGAN KEPUTUSAN WAITHOODTERHADAP PEREMPUAN GENERASI MILENIAL - Pani Prihartini, - (2022)
Humans usually want marriage and in the cycle of social life marriage is something important. But in this era, many men and women are still unmarried until their 30s and it is considered a delay in getting married. Millennial generation women are now more interested in pursuing a career than getting married, so that they become independent women and do not depend on others for their lives. With the independence of a woman and her love for freedom, women are more confident and not afraid to make their own choices, including the decision to marry, postpone marriage, or not marry even though the decision is considered an unusual thing. Therefore, researchers are interested in studying the problems referred to as the phenomenon of waiting or delaying marriage that occurs among the millennial generation, especially women who are already independent or are usually independent women. The method used in this research is descriptive statistical method. The results showed that women's independence had a strong relationship with the decision to wait for millennial women. This is supported by liberal feminist theory where the theory supports freedom for women, including women's freedom to choose their life choices.